Historia de la religión de Israel (Estudio Agustiniano, 2017)
The ancient history of Israel has undergone a profound change in the last 30 years of the past century. Since the religion of Israel is historical, it also had to be radically rethought. Consequently, ancient monotheism cannot be affirmed. The religion was very much like that of the neighboring tribes. Source critique and some very interesting extrabiblical texts do not allow toseparate the religion of Israel from that of the other peoples. Polytheism must have been normal and commonly practiced. Nor is aniconism or absence of divine images credible. Archaeological discoveries confirm the existence of goddesses well into the sixth century. From this time onwards, religious and social reform decisively penetrated the Israelite society. The Yahweh movement starts only with the prophet Hosea, who was the promoter of this reform. The cleansing was deep, and driven by various streams of post-exilic Judaism.
Keywords: Israelite religion; Polytheism; Monotheism; Aniconism